Vaccines in adults with autoimmune inflammatory rheumatic disease: What are the knowledge and attitudes of physicians? - Suade Özlem Badak (Archives of Rheumatology, 2022)
Objectives: The aim of this study was to evaluate the knowledge and practices about vaccination in adults with autoimmune inflammatory rheumatic diseases (AIRD) among primary care physicians (PCPs), internal medicine specialists (IMSs), and rheumatologists and to emphasize the importance of vaccination. Patients and methods: Between March 2021 and April 2021, a total of 310 IMSs, PCPs, and rheumatologists (132 males, 178 females; mean age: 37.4±9.5 years; range, 24 to 64 years) were included. A web-based questionnaire was used in the study. Results: Of the physicians, 87.7% were aware of that patients with AIRD were among adults with vaccination indications, but 53.9% reported that they knew about recommended vaccines, and 53.2% recommended vaccines to their patients. The most common reasons for not recommending vaccination were reservations about the drugs used (22.3%) and lack of information (17.7%). Those with longer practice as physicians and older physicians had less knowledge about the vaccine than the other participants. While 59.7% of the participants thought that the vaccination plans of the patients should be made by the rheumatologist, the rate of PCPs who did not prefer to apply the planned vaccines in the first step was 50.7%. A total of 50% of the participants did not recommend the administration of the COVID-19 vaccine in a primary healthcare institution to those receiving immunosuppressive therapy. Conclusion: Considering that one of the major obstacles to adult vaccination is the physician’s refusal to recommend it, our study highlights the missing points in the vaccination knowledge and approach of physicians. Providing advice on adult vaccination and immunization of risky groups to more physicians and periodic training to prevent loss of knowledge after graduation may contribute to an increase in the vaccination rate of adults with AIRD.